Effect of Social Capital on Innovation: A Mediating Role of Employee Motivation - Yazdanifar, M. (Engineering, Technology & Applied Science Research, 2018)
Enterprises’ survival depends on their ability to self-reconstruct. This reconstruction regards coordinated goals with the current situation and improved methods used to achieve these goals. Companies have to improve processes of innovation and creativity in order to adapt to changes. This study tends to examine the effect of social capital on innovation with emphasis on the mediating role of employee motivation. Through a descriptive-correlational study, 196 SSO employees in Tehran were randomly recruited and were asked to fill out relative questionnaires. The validity and reliability of the questionnaires were determined by using CFA and calculating Cronbach’s alpha. Data were tested by using descriptive tests (mean and standard deviation) and analytic tests (path analysis). The effect of social capital and employee motivation was positive and significant on organizational innovation (p